Vaginal dryness in women infected by human T-lymphotropic virus type 1: an exploratory study. Issue 2 (17th April 2023) - Martins, Adenilda Lima Lopes; de Aquino Firmino, Alisson; Boa-Sorte, Ney; Araújo, Jean Paulo Lacerda; Paixão, Taiane Silva; Viriato, Adriele Ribeiro França; Galvão-Castro, Bernardo; Grassi, Maria Fernanda Rios
Abstract: Background: Human T-lymphotropic virus type-1 (HTLV-1) causes a variety of sicca symptoms, including xeroderma, xerostomia, and xerophthalmia. Aim: We sought to evaluate vaginal dryness via the degree of perceived vaginal lubrication, vaginal hormonal cytology, and direct measurements of vaginal wetting. Methods: The research was designed as a cross-sectional study. Vaginal dryness was assessed by scores in the lubrication domain of the Female Sexual Function Index (FSFI) questionnaire and the Vaginal Maturation Index (VMI) determined by vaginal hormonal cytology, as well as the measurement of vaginal lubrication using Schirmer strips placed at the anterior vaginal wall. Medians (25th-75th percentiles) were calculated for each group and compared using a nonparametric Kruskal-Wallis test and the Dunn-Bonferroni post hoc method. Outcomes: Outcomes were detection of the presence of vaginal dryness in women who were infected or noninfected with HTLV-1. Results: HTLV-1–infected women ( n  = 72, 57 asymptomatic and 15 with HTLV-1–associated myelopathy/tropical spastic paraparesis [HAM/TSP]) and uninfected women ( n  = 49) were studied. Women with HAM/TSP had significantly lower FSFI lubrication scores than asymptomatic and uninfected women ( P  = .032). In addition, women with HAM/TSP had significantly lower VMI compared with the asymptomatic and uninfected groups ( P  = .027 and P  = .039, respectively). Clinical Implications: The results of this study show a reduction in vaginal lubrication in HTLV-1-infected women diagnosed with HAM/TSP compared with asymptomatic and uninfected women. Strengths and Limitations: The lack of a gold standard test for the diagnosis of vaginal dryness and the fact that no assessment of vaginal pH was performed were limitations of this study. The strength of the study was the comprehensive assessment of vaginal dryness from several perspectives: subjective (perception of vaginal lubrication according to the vaginal lubrication domain of the FSFI), hormonal (vaginal hormonal cytology to assess local hormone status), and the degree of vaginal moisture (direct measurement of vaginal dryness with an instrument, the Schirmer strip, already used to measure the presence of dry eye). Conclusion: HTLV-1-infected women with HAM/TSP have decreased vaginal lubrication compared with asymptomatic and uninfected women after adjusting for age.